Militarisation de l’espace et représentations sociales du conflit à Chypre du Nord - Mathieu Petithomme (Cahiers Balkaniques)
On the basis of fieldworks conducted in 2012 and 2014 in North‑Nicosia (Lefkoşa/Lefkosia) and Famagusta (Gazimağusa/Ammochostos), this paper proposes an ethnographical study of the militarization of space and of its psychosocial impact in Northern Cyprus. It suggests an anthropological redefinition of sovereignty based on its spatial dimension. It shows that the territorial control imposed by the Turkish army since 1974, though “illegal” in international law and considered as an “occupation” (işgal) by peace militants, is nevertheless important and durable in practice. The ethnography of war ruins in Varosha (Maraş) shows that the militarization modifies space’s material properties but also Turkish Cypriots’ representations of their own territory and of the Cyprus conflict. Thus, militarization impedes the return to the status quo ante bellum, while playing a performative role by helping to create the “Turkish Republic of Northern Cyprus”.